Factors influencing sustainability certification among plantation companies in Malaysia: a panel approach - Tey, Yeong Sheng; Brindal, Mark Kennion; Darham, Suryani; Ahmad Sidique, Shaufique Fahmi; Djama, Marcel (Elsevier, 2020)
The adoption of palm oil sustainability standards remains limited, especially among plantation companies. This is a concern since plantation companies are pivotal for the palm oil industry, not only because of their own production but because they form an important nucleus for smallholders. Using a panel technique, this study investigates the drivers underlying the certification of the Roundtable on Sustainable Palm Oil (RSPO) standard by plantation companies in Malaysia. We examine the period between 2007 and 2016. Panel logistics analysis allows for changes in variables, including company capacity (proportion of planted area and debt-to-equity ratio) and the time-dependent price of crude palm oil. Despite the fact that these variables influence adoption, our findings reveal that adoption is found to be elastic to changes only in proportion to the planted area. Plantation companies that have undertaken conservation efforts may present “low-hanging fruits”. Given the currently limited response to adoption, a partially targeted approach encompassing education and technical assistance, financial assistance, and regulation is recommended to create a more inclusive and enabling environment.